Web switching and international outsourcing: A matching approach - Aoife Hanley; Ingrid Ott (Kiel Institute for the World Economy (IfW), 2010)
Formulating a model comprising transportation, uncertainty and price, we describe how Web procurement is likely to boost volumes of international services vs. materials inputs. Using panel data for over 2,000 firms, we find that Web procurement increases international services outsourcing by between 1.6 and 2.5 percent for the FE and D-in-D matching estimators. These values are comparable to those obtained by Bartel et al. (2005) using different methodologies and US aggregate data. Although no existing work has yet reported effects for international materials outsourcing we find that Web procurement decreases international materials outsourcing by between 2.2 and 3.7 percent.
Keywords: L23; R34; 330; International outsourcing; heterogeneous inputs; uncertainty; price; transportation costs; propensity score matching; Beschaffung; E-Business; Internet; Outsourcing; International; Verarbeitendes Gewerbe; Schätzung; Irland